WASTEWATER EVAPORATOR POND ASSESSMENT OF «CASPI BITUM» LLP - Gusman Kenzhetayev,; Syrlybekkyzy Samal,; Lyailim Taizhanova, (Academic Journal of Physical and Chemical Sciences, 2020)
The dynamics and level of pollution of the wastewater evaporator pond of the bitumen plant were studied in 2018-2019. The chemical composition of the waste water (WW) pond was determined by 8 indicators. The average annual indicators of the studied harmful substances in the water exceeded the permissible level from 1.1 to 21.9 times. At the same time, exceeding standards were registered for substances of 3 and 4 hazard classes: total iron - up to 2.8 times, petroleum products - up to 1.7 times. The content of anionic surface active agents (SAA) in the evaporator pond with an average degree of oxidation was recorded in excess of the maximum permissible concentration (MPC) by 2.0 times, 2.13 times, and 2.32 times on average over the years at points 1, 2, and 3, respectively. The average values of biochemical oxigen demand/chemical oxigen demand (BOD5/COD) for 2018- 2019 were as follows for the studied points of the evaporator pond: at point 1 (water outlet) - 0.215, at point 2 (South-Eastern part) - 0.195, at point 3 in the area of the sand massif - 0.21, and under the condition of BOD5/COD<0.5 it means that the WW is over by resistant to oxidation compounds. This requires accelerating the evaporation process. A heliotechnical system of translucent coverings has been developed and offered for intensifying the evaporation process and isolating harmful substances from contacts with the biosphere. This system is environmentally and economically feasible.